Efektivitas Pembelajaran Pak Dengan Media Interaktif Berbasis Articulate Storyline 3 Kelas VIII SMP Yoannes XXIII Semarang - Olwadus Waspada Laia; Andarweni Astuti; Hartutik Hartutik (Universitas Katolik Widya Karya Malang, 2023)
The research conducted at SMP Yoannes XXIII Semarang aims to determine the effectiveness of implementing interactive media, specifically Articulate Storyline 3, in PAK learning. This True Experimental Design study selected class VIII C, consisting of 28 students, as the experimental group, and class VIII B, with 27 students, as the control group at SMP Yoannes XXIII Semarang. The analyzed results of the research indicate that the posttest scores of students who participated in interactive media learning were 82.50 points, significantly higher than the control group, which scored only 70.19 points. The N-Gain test also demonstrates the increased effectiveness of interactive media, with a score of 59.09 points, categorized as fairly effective. The influence of curiosity on student learning outcomes using this learning media was found to be 66.6%. In conclusion, based on the data analysis findings, students in class VIII at SMP Yoannes XXIII Semarang benefited from the use of interactive media based on Articulate Storyline 3 in their learning process.